Circadian Control of Metabolism by the Clock Component TOC1 - Cervela-Cardona, Luis; Yoshida, Takuya; Zhang, Youjun; Okada, Masaaki; Fernie, Alisdair; Mas, Paloma (Frontiers in Plant Science, 2021)
Photosynthesis in chloroplasts during the day and mitochondrial respiration during the night execute nearly opposing reactions that are coordinated with the internal cellular status and the external conditions. Here, we describe a mechanism by which the Arabidopsis clock component TIMING OF CAB EXPRESSION1 (TOC1) contributes to the diurnal regulation of metabolism. Proper expression of TOC1 is important for sustaining cellular energy and for the diel and circadian oscillations of sugars, amino acids and tricarboxylic acid (TCA) cycle intermediates. TOC1 binds to the promoter of the TCA-related gene FUMARASE 2 to repress its expression at night, which results in decreased fumarate accumulation in TOC1 over-expressing plants and increased in toc1-2 mutant. Genetic interaction studies confirmed that over-expression of FUMARASE 2 in TOC1 over-expressing plants alleviates the molecular and physiological energy-deprivation phenotypes of TOC1 over-expressing plants. Thus, we propose that the tandem TOC1-FUMARASE 2 is one of the mechanisms that contribute to the regulation of plant metabolism during the day and night.